Return on assets and debt-to-equity ratio on dividend yield using Earning Per Share as a Moderating Variable at PT. Indofood Sukses Makmur Tbk - Rahmah, Umi; Riassy Christa, Usup; Nugroho, Sanjayanto (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
The purpose of this study was to determine the effect of Return On Assets (ROA), and Debt to Equity Ratio (DER) on Dividend Yield, with Earning Per Share (EPS) as a moderating variable. This study uses secondary data, namely in the form of financial statement data of PT. Indofood Sukses Makmur Tbk. The technique used is linear regression analysis and moderation regression analysis by utilizing the SPSS 26 program. The results showed that Return On Assets (ROA) has a positive but insignificant effect, Debt to Equity Ratio (DER) has a positive and significant effect, Earning Per Share (EPS) has an effect but is not significant on the relationship between Return On Assets (ROA) and Dividend Yield, and Earning Per Share does not affect the relationship between Debt to Equity Ratio (DER) and Dividend Yield. So to increase Dividend Yield, the company can increase the Debt to Equity Ratio (DER)